2016
DOI: 10.1002/j.1681-4835.2016.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing IT to Enhance Knowledge Sharing for School Educators in Developing Countries

Abstract: Knowledge has been considered a critical factor for any organization's survival however its retention and utilization has remained a challenge to many organizations in developing countries education institutions inclusive. These challenges are mostly attributed to the fact that knowledgeable employees often leave organizations before they could share their valuable knowledge and expertise. In schools of developing countries in particular, educators struggle for subsistence and many leave to seek for greener pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Robbins (2005) further define OC as the dynamics in the behaviour, reaction and working relationships of employees coming from different social orientations, who are situated in different hierarchal positions and command varying degrees of positional influence within the organisation. Ultimately, how these individuals work together determines the effectiveness or lack thereof of the knowledge sharing culture in an organisation (Argote, 2011;Attar, 2020;Ferdinandus et al, 2015;Kalema et al, 2016). Robbins (2005) argue that in an organisational setting the soundness or lack thereof of the culture tends to show itself.…”
Section: Synchronising Knowledge Sharing Organisational Culture and L...mentioning
confidence: 99%
See 1 more Smart Citation
“…Robbins (2005) further define OC as the dynamics in the behaviour, reaction and working relationships of employees coming from different social orientations, who are situated in different hierarchal positions and command varying degrees of positional influence within the organisation. Ultimately, how these individuals work together determines the effectiveness or lack thereof of the knowledge sharing culture in an organisation (Argote, 2011;Attar, 2020;Ferdinandus et al, 2015;Kalema et al, 2016). Robbins (2005) argue that in an organisational setting the soundness or lack thereof of the culture tends to show itself.…”
Section: Synchronising Knowledge Sharing Organisational Culture and L...mentioning
confidence: 99%
“…Based on these accounts, it can be concluded that effective knowledge sharing culture injects positive energy into the organisation by improving employee's attitudes towards organisational learning, personal growth and development; and building and sustaining an ongoing learning culture, while also ensuring that critical tacit knowledge is being absorbed into organisational knowledge. While the concept of KM and its processes are adequately researched in the world's developed schooling contexts, there is a consensus that little is known about knowledge sharing (Kalema et al, 2016) and the applicability of KM processes in a South African schooling system (Gxwati, 2011). This warrants the need for developing an understanding on how effective or ineffective KM processes are in the South African schooling contexts.…”
Section: Introductionmentioning
confidence: 99%
“…(Primary schools serve children from ages 6-13; secondary ones from ages 14-18; and combined ones from ages 6-15.) As indicated above, a literature review of research on KM in South Africa indicates a paucity of documented body of work on KM where the schooling system is a focus of attention -with Moloi's (2010) and Kalema, Motsi and Motjolopane's (2016) work being exceptions. Meanwhile, on a global level, De Angelis remarks that indeed scant attention has been given to public sector KM more generally, and the few examples that exist do not "provide [sufficiently] rich data on the strategies and experiences of those engaged in the process at the organizational level" (2013, p. 8).…”
Section: Effective and Ethical Management: Ba And Ubuntu As A Potenti...mentioning
confidence: 99%
“…A radical shift is required in the organization’s culture to make investments on new technologies and to focus on all levels of the organization (Seth et al , 2018). Therefore, organizations need to build a flexible culture to invest in new technologies that allow individuals of various specialties, expertise and skills to access the same information and to encourage each other in all aspects of work (Kalema et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%